2018
DOI: 10.1016/j.jtcvs.2018.02.038
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and prognostic factors for postsurgical pulmonary vein stenosis in the current era

Abstract: Postsurgical pulmonary vein stenosis still has a guarded prognosis in the current era. The sutureless technique is an independent protective factor against restenosis. The severity of the residual disease evaluated by a new severity score is an independent risk factor for poor outcomes regardless of surgical technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 26 publications
1
36
0
Order By: Relevance
“…Echocardiography. Each PV was assessed by echocardiography according to a standardized imaging protocol described by Kalfa et al [6], consisting of three components: (1) severity of disease measured by mean echocardiographic pressure gradient and (2) extent of stenosis in each individual pulmonary vein (PV) and (3) uni-or bilateral extent of the disease. ECHSA Score was used to summarize the findings.…”
Section: Methodsmentioning
confidence: 99%
“…Echocardiography. Each PV was assessed by echocardiography according to a standardized imaging protocol described by Kalfa et al [6], consisting of three components: (1) severity of disease measured by mean echocardiographic pressure gradient and (2) extent of stenosis in each individual pulmonary vein (PV) and (3) uni-or bilateral extent of the disease. ECHSA Score was used to summarize the findings.…”
Section: Methodsmentioning
confidence: 99%
“…The sutureless technique may be an effective technique even for the primary repair of TAPVC [3]. Kalfa and colleagues [4] presented an analysis of multi-institutional experience of 14 European and North American institutions with postsurgical pulmonary vein stenosis (PSPVS). They demonstrated that residual severity of the disease is the main prognostic factor for adverse outcomes regardless of the repair method.…”
Section: Fig 1 Selective Pulmonary Vein Angiography and Rpv Balloonmentioning
confidence: 99%
“…Peripheral lesions located beyond the first order division within the pulmonary parenchyma are generally beyond the surgeon's reach, rendering the sutureless technique inapplicable in the treatment of distal disease. Further, the results for the sutureless repair with primary PVS and in patients with severe pulmonary vein disease are not as encouraging as with postoperative PVS …”
Section: Introductionmentioning
confidence: 99%
“…Further, the results for the sutureless repair with primary PVS and in patients with severe pulmonary vein disease are not as encouraging as with postoperative PVS. 12 Given the poor prognosis of this disease with the current available technology, our center sought to evaluate the use of drug eluting stents (DES) as a primary mode of therapy for patients with PVS. The purpose of the present study is to review our experience with DES in children with congenital or postoperative PVS after repair of APVR and to compare this modality of treatment with BMS implantation, specifically looking at the incidence of restenosis, reintervention rates, ultimate impact on pulmonary vein patency and patient outcomes.…”
mentioning
confidence: 99%